(Study on the Effect Of Various Heat Treatment Process to the Refined Deodorized Bleached Castor Oil) - Rizal Alamsyah; Mirna Isyanti; Yuniarti - (Warta Industri Hasil Pertanian, 2007)
Heat treatment is one of the important factors in refining castor oil since it was able to coagulate amino acid so that thefat could be easily extracted. The heat treatment conducted were roasting, steaming, and drying. It was conducted before pressing of castor seed. Meanwhile refining castor oil consist of cleaning, grading, drying, pressing, deguming, sentrifusing mixing, bleaching and filter screening (vacuum), washing and quality testing. Pressing of castor kernel was conducted with 50 tons hydrolics press and screw press. Refined castor oil treatment with oven temperature 60 degree celcius for 1 hour showed the higest yield from the other treatment and also the clearer colour. Various concentration and combinationof oxidator was used to produce modified castor oil from refined castor oil. Oxidator used were H2O2 (3% and 5%), KMnO4 (3% and 5%). The best result oxidized castor oil was processed from refined castor oil and oxidator H2O2 3% with 1:5 comparison of volume.